The sacred books of the Jews / Harry Gersh. - Gersh, Harry (New York : Stein and Day, 1968)
Central ideas and influence of the Torah, the Talmud, the Kabbalah, and other less-known writings.
The Bible : sources and authors --
The Bible as history --
The Bible as law --
The prophets --
Wisdom literature in the Bible --
The Talmud : history and authors --
The Talmud : Mishnah, transcription of the oral law --
The Talmud : Gemarah, commentary on the oral law --
Midrash : the Aggadic tales --
Commentaries and codes --
The Responsa : the living law --
The challenge of philosophy : the guide of the perplexed --
Mysticism : the Kabbalah and the Zohar --
Liturgy : the Siddur.
Keywords: Jewish religious literature -- History and criticism; Judaism -- Doctrines